Kidung kaki tuwa sebuah kajian konvensi budaya dan nilai I.Nyoman Sukartha, I.B.Mayun, Wayan Rupa; penyunting, Kencana Sembiring P - SUKATHA, I.Nyoman; Mayun, I.B; Rupa, Wayan; Sembiring P., Kencana (1996)
x, 108 hlm 21 cm